2023
DOI: 10.3390/f14071429
|View full text |Cite
|
Sign up to set email alerts
|

Responses and Post-Recovery of Physiological Traits after Drought–Heatwave Combined Event in 12 Urban Woody Species

Abstract: The frequency and intensity of droughts combined with heatwave events have increased under climate change, increasing destruction in urban areas and leading to severe impacts on urban plants. These impacts remain poorly understood at the species level. Here, we investigate the effects of a drought–heatwave event on 12 urban woody species using in situ records of the dynamic changes in physiological traits in the field before, during and after the drought–heatwave event to assess resistance and resilience to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 76 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…This stability may be attributed to urban tree growth trajectories being better suited to high-temperature conditions, coupled with the complexity of growth-driving factors for urban plants. A study found that urban environments promote plant resistance to high temperatures [ 13 ], which might be associated to diverse planting methods, soil types, and fertilization practices, each significantly influencing plant growth [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This stability may be attributed to urban tree growth trajectories being better suited to high-temperature conditions, coupled with the complexity of growth-driving factors for urban plants. A study found that urban environments promote plant resistance to high temperatures [ 13 ], which might be associated to diverse planting methods, soil types, and fertilization practices, each significantly influencing plant growth [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be attributed to their distinct resource allocation strategies [ 13 ]. Our research demonstrated that evergreen tree species adopted a more conservative resource allocation approach ( Figure 4 a), progressively favoring structural components as they transitioned from rural to urban areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations